2009
DOI: 10.1021/pr800637z
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Expression Signature Distinguishes Cancerous and Nonmalignant Tissues in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is an aggressive liver cancer but clinically validated biomarkers that can predict natural history of malignant progression are lacking. The present study explored the proteome-wide patterns of HCC to identify biomarker signature that could distinguish cancerous and non-malignant liver tissues. A retrospective cohort of 80 HBV-associated HCC was included and both the tumor and adjacent non-tumor tissues were subjected to proteome-wide expression profiling by 2-DE method. The subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 57 publications
(92 reference statements)
2
48
0
Order By: Relevance
“…Recently, the cysteine protease cathepsin B has been associated with metastasis and poor prognosis in multiple cancer types, including cervical, colorectal, and ovarian carcinomas and highgrade glioma (15,23,26,29,34,37,38,45). Using a proteomic signature model, Lee et al have identified cathepsin B as one of six biomarkers allowing discrimination of HCC from nonmalignant and normal liver tissues with high accuracy (19). However, what role this protein serves in HCC development and progression has not been explored by this group or other investigators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the cysteine protease cathepsin B has been associated with metastasis and poor prognosis in multiple cancer types, including cervical, colorectal, and ovarian carcinomas and highgrade glioma (15,23,26,29,34,37,38,45). Using a proteomic signature model, Lee et al have identified cathepsin B as one of six biomarkers allowing discrimination of HCC from nonmalignant and normal liver tissues with high accuracy (19). However, what role this protein serves in HCC development and progression has not been explored by this group or other investigators.…”
Section: Discussionmentioning
confidence: 99%
“…This led us to investigate whether the HBSP could interact with CTSB in the context of hepatoma cells to affect cell migration, invasion, and metastasis, all of which can be modulated by CTSB acting directly and indirectly on extracellular matrix (ECM) component remodeling and degradation (26,47). CTSB is a lysosomal cysteine protease that plays an important role in physiological protein turnover and processing (19,41). In nonmalignant cells, CTSB is mainly stored in the lysosome, whereas in malignant cells, CTSB redistributes into exocytic vesicles at the cell periphery, leading to its secretion and association with binding partners on the tumor cell surface (22,33).…”
mentioning
confidence: 99%
“…In our earlier proteomic studies, 11,28,29 we identified members of the heat shock family proteins that are often upregulated in HCC and associated prognostic outcomes, and mortalin as a marker for predicting HCC metastasis and recurrence. In our study, we demonstrated the interaction of mortalin and p53 in liver tumors and HCC-derived cell lines that harbored mutant p53.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry was performed as previously described with modifications (Lee et al, 2006(Lee et al, , 2009b. Tissue sections were deparaffinized by submerging the slides in xylene and rehydrated in decreasing concentrations of ethanol (100% followed by 90 and 75%, each twice).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Western blot (Lu et al, 2011) and immunohistochemical analysis (Lee et al, 2006(Lee et al, , 2009b were performed as described previously.…”
Section: Dkk4 Antibody Specificitymentioning
confidence: 99%